Pengungkapan Aktivitas Corporate Social Responsibility Di Industri Kesehatan dan Farmasi Di Masa Pandemi Covid-19 - Monica Adiya Victorie; Arthik Davianti (Politeknik Ganesha Medan, 2022)
This study aims to study CSR disclosure practices by the four pharmaceutical companies listed on the Indonesia Stock Exchange, which consist of PT Indofarma Tbk, PT Sido Muncul Tbk, PT Kalbe Farma Tbk and Phapros Tbk. The basis of disclosure analysis uses the GRI 403 standard as a guideline in the aspect of disclosure. The case occurred due to the Covid-19 pandemic so that it directly affected the community and employees. This makes the company's disclosure practices can have a positive effect on the community and employees. This study uses descriptive qualitative with qualitative content analysis techniques on the sustainability reports of observed companies published in 2019-2020. The results of the analysis show the disclosure of occupational safety and health aspects through ten codes. The codes are health, environment, medicine, risk mitigation, prevention, training, quality of health, accidents, workers, and disease. The code is based on the disclosure standard GRI 403: Occupational Safety and Health. Using the theory of legitimacy, namely companies disclose information voluntarily when the law does not force them, it states an exchange between the company and the community which is called a contract.